(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Coarctation of the aorta (CoA) is a congenital narrowing of the aortic lumen, usually diagnosed in childhood. Adult presentation is uncommon and often associated with hypertension, extensive collateral circulation, and complex vascular anatomy, making conventional repair challenging. Case description and management: We report a 21-year-old man (body mass index, 21 kg/m²) with a 6-month history of headache and palpitations. He had severe hypertension, tachycardia, diminished femoral pulses, and a systolic murmur, but no hypertensive target-organ damage or secondary causes. Transthoracic echocardiography and computed tomography angiography confirmed severe CoA distal to the left subclavian artery, a patent ductus arteriosus, post-stenotic dilatation, and a bicuspid aortic valve. Preoperative antihypertensive therapy was initiated. The patient underwent off-pump extra-anatomic ascending-to-descending aortic bypass with patent ductus arteriosus ligation via median sternotomy and left anterior thoracotomy. Cardiopulmonary bypass was kept on standby, and distal perfusion was maintained throughout the procedure. Postoperatively, antihypertensive therapy was titrated according to upper-limb blood pressure, renal function, and lower-limb perfusion. Echocardiography at one-month follow-up confirmed a functioning graft, a peak gradient of 10 mmHg, and no residual shunt th follow-up echocardiography confirmed a functioning graft, peak gradient of 10 mmHg, and no residual shunt. Conclusion: Extra-anatomic aortic bypass is a safe and effective alternative for adults with CoA and complex anatomy, minimising surgical risk while providing durable relief. This case highlights the feasibility of surgical correction and favourable outcomes in adults presenting with CoA.